2000
DOI: 10.1152/jn.2000.83.2.907
|View full text |Cite
|
Sign up to set email alerts
|

Directionality Derived From Pinna-Cue Spectral Notches in Cat Dorsal Cochlear Nucleus

Abstract: We tested two hypotheses to determine whether dorsal cochlear nucleus (DCN) neurons are specialized to derive directionality from spectral notches: DCN neurons exhibit greater spectral-dependent directionality than ventral cochlear nucleus (VCN) neurons, and spectral-dependent directionality depends on response minima (nulls) produced by coincidence of best frequency (BF) and spectral-notch center frequency. Single-unit responses to 50-ms noise and tone bursts were recorded in barbiturate-anesthetized cats (BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
6
51
0
1
Order By: Relevance
“…1D) predict that these stimuli will produce a spatial receptive field in which excitatory discharge rates parallel the unit's preferred notch frequency contour. A similar pattern of inhibitory activity has been previously described for DCN type IV units (Imig et al 2000).…”
Section: Processing and Perception Of Spectral Cues For Sound Localizsupporting
confidence: 80%
See 1 more Smart Citation
“…1D) predict that these stimuli will produce a spatial receptive field in which excitatory discharge rates parallel the unit's preferred notch frequency contour. A similar pattern of inhibitory activity has been previously described for DCN type IV units (Imig et al 2000).…”
Section: Processing and Perception Of Spectral Cues For Sound Localizsupporting
confidence: 80%
“…Electrophysiological studies in cats have shown that the projection neurons of the dorsal cochlear nucleus (DCN) are especially sensitive to spectral notches Imig et al 2000). When tested with pure tones, DCN principal cells exhibit a type IV frequency response map that is characterized by inhibitory responses at most combinations of frequency and level.…”
Section: Introductionmentioning
confidence: 99%
“…Neurophysiological studies in other mammalian species have identified neural populations that perform wideband spectral integration in the dorsal cochlear nucleus (DCN;Young et al 1992;Imig et al 2000) and the central nucleus of the inferior colliculus (ICC; Davis et al 2003;Chase and Young 2005). Surgical lesions of this spectral processing pathway produce localization deficits that are most obvious for the identification of sound source elevation (Sutherland et al 1998;May 2000).…”
Section: Role Of Monaural Spectral Cuesmentioning
confidence: 99%
“…Type IV units also respond with inhibition when a spectral notch is placed at their BF (Spirou and Young 1991). By virtue of their unusual sensitivity to narrowband peaks and notches, such as those added to sounds by the directionally dependent filtering properties of the pinna (Musicant et al 1990;Rice et al 1992), DCN principal cells are thought to serve a role in the detection of the spatial location of sound sources Imig et al 2000). Consistent with this interpretation, lesioning the output pathway of the DCN disrupts the sound orientation behaviors of cats (Sutherland et al 1998;May 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The latencies of these inhibitory responses are suggestive of mono-and disynaptic connections from the contralateral cochlear nucleus. Finally, single-unit studies have demonstrated that DCN neurons are sensitive to acoustic stimulation of the contralateral ear (Mast 1970(Mast , 1973Young and Brownell 1976;Evans and Zhao 1993;Joris and Smith 1998;Imig et al 2000). Some units are excited by monaural stimulation of the contralateral ear, but others are inhibited.…”
Section: Introductionmentioning
confidence: 99%